2024
DOI: 10.1002/epi4.12924
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of status epilepticus: A systematic review

Rohan Jha,
Sarah E. Blitz,
Melissa M. J. Chua
et al.

Abstract: Status Epilepticus (SE), unresponsive to medical management, is associated with high morbidity and mortality. Surgical management is typically considered in these refractory cases. The best surgical approach for affected patients remains unclear; however, given the lack of controlled trials exploring the role of surgery. We performed a systematic review according to PRIMSA guidelines, including case reports and series describing surgical interventions for patients in SE. Cases (157 patients, median age 12.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Several other approaches have been proposed to treat refractory status epilepticus and super-refractory status epilepticus, including immunotherapy, neuroactive steroids, neuromodulation, magnesium infusion, pyridoxine infusion, hypothermia, ketogenic diet, electroconvulsive therapy, inhaled anesthetics, transcranial direct current stimulation, and surgical intervention if a definitive seizure focus has been clearly recognized ( table 6-10 ). 60,70–77 …”
Section: Management Of Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other approaches have been proposed to treat refractory status epilepticus and super-refractory status epilepticus, including immunotherapy, neuroactive steroids, neuromodulation, magnesium infusion, pyridoxine infusion, hypothermia, ketogenic diet, electroconvulsive therapy, inhaled anesthetics, transcranial direct current stimulation, and surgical intervention if a definitive seizure focus has been clearly recognized ( table 6-10 ). 60,70–77 …”
Section: Management Of Status Epilepticusmentioning
confidence: 99%
“…69 Other Interventions to Treat Super-refractory Status Epilepticus Several other approaches have been proposed to treat refractory status epilepticus and super-refractory status epilepticus, including immunotherapy, neuroactive steroids, neuromodulation, magnesium infusion, pyridoxine infusion, hypothermia, ketogenic diet, electroconvulsive therapy, inhaled ◆ Vagus nerve stimulation ◇ Not widely used ◇ A systematic review 72 found that 74% of 38 patients with refractory status epilepticus or super-refractory status epilepticus had seizure cessation after acute VNS implantation ◆ Deep brain stimulation ◆ Limited evidence ◆ Some data suggest that deep brain stimulation can control seizures in patients with epilepsy ◆ Target the anterior thalamic nucleus in super-refractory status epilepticus Pyridoxine (vitamin B 6 ) infusion ◆ Pyridoxine is required for the production of GABA ◆ Up to 80% of patients with established status epilepticus have pyridoxine deficiency 44 ◆ There are no clear dosing data ◆ Might be most beneficial in early status epilepticus (stage 1) Resective neurosurgery 76 ◆ Consider when an epileptogenic zone has been identified ◆ Can include focal, lobar, or multilobar resection; corpus callosotomy; hemispherectomy; or multiple subpial transections, either alone or in combination with focal resection Therapeutic hypothermia ◆ HYBERNATUS multicenter randomized controlled trial 77 failed to show any benefit in functional outcome at 3 months ◆ Antiseizure medication levels should be followed as hypothermia reduces drug clearance Transcranial direct current stimulation ◆ Emerging data for use in super-refractory status epilepticus ◆ Recent pilot study 73 showed that 10 patients with refractory status epilepticus benefited from 2-mA, 20-minute transcranial direct current stimulation sessions (ie, a reduction of 50% of median ictal epileptiform discharge rate per patient per session and a reduction of 25% in the immediate period after the intervention)anesthetics, transcranial direct current stimulation, and surgical intervention if a definitive seizure focus has been clearly recognized (TABLE 6-10) 60,[70][71][72][73][75][76][77]…”
mentioning
confidence: 99%